IL-10 enhances expression of the IL-2 receptor alpha chain on T cells. - Cohen, S; Katsikis, P; Feldmann, M; Londei, M (1994)
Interleukin-10 (IL-10) has various immunomodulatory actions depending on the target cell type. Some of these effects have been shown to be owing to its ability to down-regulate surface expression of markers, for example HLA-DR on macrophages and CD25 (IL-2 receptor alpha chain) on B cells. In this report we show that preincubation of IL-10 for 24 hr up-regulates expression of the activation marker CD25, but not HLA-DR on cloned T cells of various phenotypes such as CD4+, CD8+, CD4- CD8- alpha beta and gamma delta T-cell receptor (TCR)-expressing cells. This up-regulation of CD25 was accompanied by an increase in the T cells IL-2-dependent proliferative response in 63% of the CD4+ clones and 100% of the CD8+, CD4-, CD8- alpha beta and gamma delta TCR+ clones analysed. IL-10 was also shown to be at least partly responsible for the up-regulation of CD25 on mitogen-activated peripheral blood mononuclear cells, suggesting that IL-10 has this CD25 modulatory effect within a more physiological environment. Our data suggest that IL-10 can have a multitude of effects on human T cells, and should not be considered exclusively as an immunoinhibitory cytokine.